The Effect of Pecha Kucha Presentations on Students’ English Public Speaking Anxiety (2017)
The objective of this study is to investigate the effect of the Pecha Kucha presentation format on English as foreign language learners’ public speaking anxiety. The participants were 49 students in the English Translation and Interpretation Department of a state university in Turkey. A pre- and post-test experimental research design was used in this study. Students were given a questionnaire as the pre-test prior to the preparation of their presentations and as the post-test immediately following the presentation in the classroom. According to the paired samples statistics, students’ English public speaking anxiety was reduced significantly as a result of their experience using the Pecha Kucha presentation format. It was concluded that this presentation format can be incorporated into the English as a Foreign Language classroom.